SURVEI MANAJEMEN INDUSTRI OLAHRAGA ARUNG JERAM DI BANNYUWOONG ADVENTURE KABUPATEN BANJARNEGARA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this research is to know the description of management includes planning, organizing, directionand supervision of the management of sports industry in Bannyuwoong Banjarnegara Regency Adventure. Aswell as knowing the level of satisfaction of visitors to the service in the Bannyuwoong Adventure. This researchuses qualitative as well as quantitative, descriptive approach as a secondary or additional data. Location of theresearch in Bannyuwoong Banjarnegara district Adventure. The targets in this study i.e., managers,employees, visitors, and rafting Instructor. Data collection methods used i.e., observation, interview,Questionnaire and Documentation. The results of this study are 1) Adventure Bannyuwoong managementplanning is already well underway in accordance with the objectives of the planning function. 2) Bannyuwoongmanagement Organizing Adventure is already well underway in accordance with its function. 3) processmanagement briefing Bannyuwoong Adventure is going well as appropriate in accordance with the directives ofthe Chief Manager in Bannyuwoong. 4 Bannyuwoong management) control is already running well evidencedby monitoring employee performance, as well as surveillance equipment and supplies. 5) Visitors felt satisfiedwith the services and facilities found in Bannyuwong Adventure. The conclusion of this research is the processof planning, organizing, direction, and supervision of management in Bannyuwoong Adventure runs well andhas been carrying out the functions and processes, as appropriate. Visitors felt satisfied with the service of themanagement of the Bannyuwoong Adventure.